A efetividade dos direitos humanos em face da eugenia genética no teste pré-implantacional - Cotomacci, Gustavo (2024)
The dissertation investigates the effectiveness of human rights in the face of genetic eugenics within the context of pre-implantation testing. The analysis, through bibliographic and jurisprudential references, reveals the evolution of human rights and bioethics, which were established to protect human dignity, particularly following the atrocities of the world wars and advancements in medicine and biotechnology. The intersection between bioethics and human rights is crucial to ensuring that scientific progress respects and promotes human dignity, especially concerning genetic eugenics and assisted reproduction. The dissertation highlights the role of biolaw, an interdisciplinary field that regulates the ethical and legal issues associated with biotechnological innovations, seeking to balance scientific advancements with ethical values. Assisted reproduction, facilitated by biotechnology, raises significant ethical dilemmas, such as embryo selection, which can compromise equality and human dignity. The critical analysis indicates that despite technological advances, socioeconomic disparities persist, limiting equitable access to these treatments. The lack of specific regulation underscores the urgent need for public policies that protect and promote reproductive rights in a fair and equal manner. The decision of the Brazilian Supreme Federal Court in ADI 3510/DF, which permits research with embryonic stem cells, exemplifies the ethical and legal challenges involved. The dissertation concludes that the effectiveness of human rights in the face of genetic eugenics in pre-implantation testing depends on the responsible use of technologies, adequate regulation, and a continuous commitment to ethical values that respect human dignity. The harmony between science, law, and ethics is essential to ensure that scientific innovation benefits humanity without compromising the fundamental values of society